Scalable carbon nanotube growth and design of efficient catalysts for Fischer-Tropsch synthesis - Almkhelfe, Haider H. (Kansas State University, 2017)
The continued depletion of fossil fuels and concomitant increase in greenhouse gases have encouraged worldwide research on alternative processes to produce clean fuel. Fischer-Tropsch synthesis (FTS) is a heterogeneous catalytic reaction that converts syngas (CO and H₂) to liquid hydrocarbons. FTS is a well-established route for producing clean liquid fuels. However, the broad product distribution and limited catalytic activity are restricting the development of FTS. The strong interactions between the active metal catalyst (Fe or Co) and support (Al₂O₃, SiO₂ and TiO₂) during post-synthesis treatments of the catalyst (such as calcination at ~500°C and reduction ~550°C) lead to formation of inactive and unreducible inert material like Fe₂SiO₄, CoAl₂O₄, Co₂SiO₄. The activity of FTS catalyst is negatively impacted by the presence of these inactive compounds. In our study, we demonstrate the use of a modified photo-Fenton process for the preparation of carbon nanotube (CNT)-supported Co and Fe catalysts that are characterized by small and well-dispersed catalyst particles on CNTs that require no further treatments. The process is facile, highly scalable, and involves the use of green catalyst precursors and an oxidant. The reaction kinetic results show high CO conversion (85%), selectivity for liquid hydrocarbons and stability. Further, a gaseous product mixture from FTS (C1-C4) was utilized as an efficient feedstock for the growth of high-quality, well-aligned single-wall carbon nanotube (SWCNT) carpets of millimeter-scale heights on Fe and (sub) millimeter-scale heights on Co catalysts via chemical vapor deposition (CVD). Although SWCNT carpets were grown over a wide temperature range (between 650 and 850°C), growth conducted at optimal temperatures for Co (850°C) and Fe (750°C) yielded predominantly SWCNTs that are straight, clean, and with sidewalls that are largely free of amorphous carbon. Also, low-temperature CVD growth of CNT carpets from Fe and Fe–Cu catalysts using a gaseous product mixture from FTS as a superior carbon feedstock is demonstrated. The efficiency of the growth process is evidenced by the highly dense, vertically aligned CNT structures from both Fe and Fe–Cu catalysts even at temperatures as low as 400°C–a record low growth temperature for CNT carpets obtained via conventional thermal CVD. The use of FTS-GP facilitates low-temperature growth of CNT carpets on traditional (alumina film) and nontraditional substrates (aluminum foil) and has the potential of enhancing CNT quality, catalyst lifetime, and scalability. We demonstrate growth of SWCNT carpets with diameter distributions that are smaller than SWCNTs in conventional carpets using a CVD process that utilizes the product gaseous mixture from Fischer-Tropsch synthesis (FTS-GP). The high-resolution transmission electron microscopic (HR-TEM) and Raman spectroscopic results reveal that the use of a high melting point metal as a catalyst promoter in combination with either Co (1.5 nm ± 0.7) at 850ºC or Fe (1.9 nm ± 0.8) at 750ºC yields smaller-diameter SWCNT arrays with narrow diameter distributions. Scalable synthesis of carbon nanotubes (CNTs), carbon nanofibers (CNFs), and onion like carbon (OLC) in a batch reactor using supercritical fluids as a reaction media is demonstrated. The process utilizes toluene, ethanol, or butanol as a carbon precursor in combination with ferrocene that serves as a catalyst precursor and a secondary carbon source. The use of supercritical fluids for growth does not only provide a route for selective growth of a variety of carbon nanomaterials, but also provides a unique one-step approach that is free of aggressive acid treatment for synthesis of CNT-supported metallic nanoparticle composites for catalysis and energy storage applications.
Keywords: Fischer-Tropsch synthesis; Synthesis carbon nanomaterials; Chiral and diameter control of single wall carbon nanotubes (SWCNTs); Carbon nanotubes (CNTs); Gaseous product mixture from Fischer-Tropsch synthesis (FTS-GP)